2023
DOI: 10.1186/s40478-023-01657-z
|View full text |Cite
|
Sign up to set email alerts
|

Myopathologic trajectory in Duchenne muscular dystrophy (DMD) reveals lack of regeneration due to senescence in satellite cells

Nastasia Cardone,
Valentina Taglietti,
Serena Baratto
et al.

Abstract: Duchenne muscular dystrophy (DMD) is a devastating X-linked muscular disease, caused by mutations in the DMD gene encoding Dystrophin and affecting 1:5000 boys worldwide. Lack of Dystrophin leads to progressive muscle wasting and degeneration resulting in cardiorespiratory failure. Despite the absence of a definitive cure, innovative therapeutic avenues are emerging. Myopathologic studies are important to further understand the biological mechanisms of the disease and to identify histopathologic benchmarks for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In this study, we found that individuals diagnosed with dependency exhibit a pro-inflammatory phenotype characterized by the increased expression of Caspase-1, IL-6, IL-1ß, as well as an elevation in the presence of CD68 + inflammatory cells. The senescence secretory profile plays a pivotal role in the initiation and advancement of various myopathies [72,73]. Additionally, we found high levels of protein expression of cell-cycle inhibitor p16 INK4a indicating an increase in senescence cells in sarcopenic muscle from DP.…”
Section: Discussionmentioning
confidence: 59%
“…In this study, we found that individuals diagnosed with dependency exhibit a pro-inflammatory phenotype characterized by the increased expression of Caspase-1, IL-6, IL-1ß, as well as an elevation in the presence of CD68 + inflammatory cells. The senescence secretory profile plays a pivotal role in the initiation and advancement of various myopathies [72,73]. Additionally, we found high levels of protein expression of cell-cycle inhibitor p16 INK4a indicating an increase in senescence cells in sarcopenic muscle from DP.…”
Section: Discussionmentioning
confidence: 59%
“…This correlation was even stronger when analyzing samples from the oldest 33-wo mice. A gradual increase in necrosis has been reported in the myo bers of DMD patients with aging, along with decreasing regenerative abilities due to the senescence of satellite cells [71]. Thus, progressive impairment of the surrounding non-supplemented DMD bers with aging may have provided a stronger impact on the remaining dystrophin supplemented-DMD bers.…”
Section: Discussionmentioning
confidence: 98%
“…They possess self-renewing features and can generate myoblasts. Nevertheless, they lose their regenerative properties during the progression of DMD [ 66 ]. Investigating the miRNA expression profile of satellite cells demonstrated that DMD alters the expression of these molecules.…”
Section: Micrornas In the Pathogenesis Of Duchenne Muscular Dystrophymentioning
confidence: 99%